Existential Therapy and the Contextual Model: Unified by Presence, Flexibility, and Meaning-Making - Anthony Cameron (International Journal of Psychotherapy Practice and Research, 2025)
This article offers a literature review and theoretical synthesis and application of existential therapy and the contextual model. It reviews the contextual factors that may be predictive of positive therapy outcomes in general, identifies distinct types of existential therapy, highlights core commonalities in these existential branches, and explores how the main aims of the existential therapy approach may be foundational in facilitating improved mental health treatment outcomes and well-being. The author asserts that presence-both intrapersonal and interpersonal are at the heart of the contextual factors, along with flexibility, and meaning-making. This assertion has implications for therapist education, development, training, and supervision.
Keywords: Existential therapy